Effects of Dietary Nano-Composite of Copper and Carbon on Antioxidant Capacity, Immunity, and Cecal Microbiota of Weaned Ira White Rabbits - Ying-Huan Zhou; Xiao-Ping Liu; Xiao-Ming Gu; Hai-Xuan Lv; Yun Yang; Zai-Xing Cai; Bin Di; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Animals)
This experiment investigated the effects of dietary supplementation with nano-composites of copper and carbon (NCCC) on antioxidants, immune functions, and the cecum microbiota of weaned Ira white rabbits. A total of 240 weaned 35-day-old Ira white rabbits were randomly allocated to five dietary treatments (n = 6 per treatment, each replicate consisted of eight rabbits) that included the control group (CON) with a basal diet, the SAL group with 60 mg/kg salinomycin (SAL) in addition to the basal diet, and the NCCC I, II, III groups, which were supplemented with 50, 100, and 200 mg/kg NCCC, respectively, in addition to the basal diet. The test lasted for 28 d. The results showed that dietary NCCC supplementation increased the liver Cu/Zn-SOD content and up-regulated the gene expression of Cu/Zn-SOD (p < 0.05), while also reducing the content of MDA in the liver and enhancing the antioxidant capacity of Ira white rabbits. Moreover, the NCCC diet supplementation reduced the content of IL-6 and down-regulated the relative expression of IL-6 and IL-1β genes in the jejunum of Ira white rabbits (p < 0.05). In addition, the metagenomic analysis of 16 S rRNA showed significant differences in the cecal microbial structure of weaned Ira white rabbits in the NCCC III group compared with the CON, NCCC I, and NCCC II groups (p < 0.05). Firmicutes and Bacteroidetes were the dominant phyla of cecal microorganisms in weaned Ira rabbits in the NCCC diet groups. The dominant genera included unidentified Eubacteriaceae, unclassified Lachnospiraceae, Christensenellaceae, and Ruminococcus. Furthermore, the relative abundance of Ruminococcus in the NCCC I and II groups was lower than that in the CON group in the cecum of Ira white rabbits (p < 0.05). In summary, our results showed that diet supplementation with NCCC could enhance the antioxidant capacity in the liver, alleviate intestinal inflammation, and regulate the structure of intestinal flora, improving the health of Ira white rabbits.